THE EFFECT OF CONSUMING FE TABLETS AND VITAMIN C COMBINATION TABLETS ON HB LEVELS IN PREGNANT WOMEN AT SHAQI CLINIC SEYEGAN IN 2023 - Saputri, Septita Dinda (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2024)
Pregnancy with anemia increases the risk of morbidity and mortality because it causes postpartum hemorrhage. In addition, mothers with anemia can experience difficulty breathing, fainting, fatigue, increased heart rate, difficulty sleeping, perinatal infections, and pre eclampsia. It also has an impact on pregnancy outcomes, namely babies can experience Intra Uterine Growth Retardation (IUGR) and LBW. The study aims to determine the effect of consuming Fe tablets and Vitamin C combination tablets on Hb levels in pregnant women. This study employed Quasy experimental research with One Group pre-test and post-test design obtained directly from respondents through questionnaires that have been prepared by researchers and the data obtained by researchers are processed using the Wilcoxon test. The results of statistical tests using the Wilcoxon test showed a P value of 0.001 (<0.05), meaning that there was an effect before and after giving FE tablets combined with vitamin C on hemoglobin levels in pregnant women. The results showed that from a total of 15 respondents who experienced anemia before treatment decreased to 2 respondents who experienced anemia after treatment. The patients are suggested to follow the instructions given by health workers when doing ANC anywhere to be obedient in taking Fe tablets combined with vitamin C as prevention and treatment of anemia during pregnancy.